Theoretical Analysis of Interaction Energy in Alginate-Capped Gold Nanoparticles Colloidal System - Foliatini Foliatini; Yoki Yulizar; Mas Ayu Elita Hafizah (Indonesian Journal of Chemistry, 2014)
Stability of Au/alginate nanocomposite was theoretically evaluated by computing various interactions energy which contributes in the system, including attraction and repulsion interaction. The results revealed that both polymer and electrostatic charges played a significant role in the stabilization, but the steric repulsion comes from polymer chain is a more effective stabilization mechanism than the electrostatic repulsion. Higher pH yielded in stronger electrostatic repulsion but when the alginate thickness is low the resulting nanocomposite was less stable in a long time period. Interaction energies for Au/alginate nanocomposite colloidal system was up to ~60 kT for alginate thickness of 1 nm, at very short particle-particle separation distance (< 1 nm). As the alginate thickness can be controlled by adjusting the alginate concentration, it can be concluded that the high stability of Au/alginate nanocomposite can be achieved by employing an appropriate amount of alginate concentration.